A spatial computable general equilibrium model for the analysis of regional climate change impacts and adaptation policies - Malte Jahn (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2014)
Climate change may affect subnational regions in very different ways. In this paper, a spatial computable general equilibrium (SCGE) model is constructed and a theoretical framework is developed to study impacts of climate change induced extreme weather events and of corresponding adaptation policies on a regional economy, focusing on water-related extreme events. The model makes use of regionalized input-output tables to represent the regional economy and takes into account different zones inside the region which have different socio-economic structures and also different levels of exposure to extreme weather. The model is used to estimate possible spatial effects and regional economic losses of climate change induced ood events in the city of Hamburg, Germany and to evaluate flood adaptation measures.
Keywords: 330